Analysis of Factors Influencing the Friction Coefficient Between Wheels and Rails of Main Train Locomotives (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article presents an analysis of the factors that influence the friction coefficient between the wheel pair and the rail, which are crucial components of the wheel motor unit of main locomotives. The research results indicate that the coupling coefficient between the rail and the wheel pair is influenced by factors such as the tire diameter of the wheel pair, the radius of the rail head, the materials of the tires and rails, the contact surfaces, the wear of the road components, the road surface wear, curved sections of the track, vertical load on the rails from the wheels, vibrations on the traction track during locomotive movement, differences in traction force conditions among moving axles, and weather conditions including air humidity, temperature, chemical composition of contaminants on contact surfaces, among others.